Fixed Point Results in Quasi-Cone Metric Spaces - Fawzia Shaddad; Mohd Salmi Md Noorani (Abstract and Applied Analysis)
The main aim of this paper is to prove fixed point theorems in quasi-cone metric spaces which extend the Banach contraction mapping and others. This is achieved by introducing different kinds of Cauchy sequences in quasi-cone metric spaces.